Dietary oxidized oils decreased growth, antioxidative capacity, and negatively affected skin color of channel catfish, Ictalurus punctatus. Issue 3 (19th August 2018) - Liang, Gaoyang; Li, Xiaoqin; Yang, Hang; Huan, Dianyu; Xu, Zhen; Leng, Xiangjun; Gao, Qiping
Abstract : Eight isolipidic diets containing 0, 20, 40, and 60 g/kg oxidized fish oil (OFO) or oxidized soybean oil (OSO) were fed to triplicate groups of channel catfish, Ictalurus punctatus, for 8 weeks to investigate the effects of oxidized oils on growth, body color, and antioxidative capacity. Lower weight gain (WG) was observed in fish fed high levels of oxidized oils (40 and 60 g/kg) ( p  < .05). At the inclusion of 40 g/kg, OFO group showed lower WG than the OSO group ( p  < .05). With the increase of dietary oxidized oils, the serum levels of malondialdehyde, total bilirubin, direct bilirubin, and activity of alanine aminotransferase and aspartate aminotransferase significantly increased ( p  < .05), but the glutathione level decreased ( p  < .05). Serum superoxide dismutase and catalase activity showed the maximum values at 20 g/kg OFO group and 40 g/kg OSO group, respectively. Compared to the 0 g/kg oxidized oil groups, both dietary oxidized oils increased the b* value (yellowness) of dorsal skin and caudal skin at 40 and 60 g/kg inclusion ( p  < .05). In conclusion, dietary oxidized oil (≥40 g/kg) decreased the growth and the antioxidative capacity and increased the yellowness of skin. OFO caused more negative effects on channel catfish than OSO at the inclusion of 40 g/kg.